Attaining Theoretical Coherence Within Relationship-Based Practice in Child and Family Social Work: The Systemic Perspective. (10th October 2019) - Coulter, Stephen; Houston, Stanley; Mooney, Suzanne; Devaney, John; Davidson, Gavin
Abstract: Social work practice has an essential, yet ambiguous, relationship with theory. This state of affairs is currently evident in the range of contemporary relationship-based practice (RBP) models being applied within Child and Family Social Work. This article argues that there is an urgent need for a theoretically coherent conceptualisation of these models to enable social work practitioners to embrace their common precepts and so enable more effective interventions. In contrast to attempts to show the distinctiveness of current models for reasons of fidelity, model identity and marketing, this unifying approach advocates for recognition of the commonality and complementarity of contemporary RBP models. The article argues that systemic theory which applies a social constructionist orientation can provide this coherence, helping social workers develop their practice in an informed way. In making this case, the emergent evidence base is noted and recommendations are made about how greater convergence and complementarity can be promoted. This article contributes to the debate about how practice and policy should be guided by theoretical ideas of coherence, alongside more utilitarian ideas advocating the importance of evidence and effectiveness.